Portuguese Adaptation of the Sources of Self-Efficacy in Writing Scale - Silva, Mariana (2021)
Writing is essential to communicate in school and daily life. However, it is a demanding task that requires motivation. Therefore, it is essential to develop students’ writing skills and self-efficacy. In the present study we aimed to adapt the Sources of Middle School Mathematics Self-Efficacy Scale (Usher & Pajares, 2009) to the writing domain and to Portuguese language, to explore the relationship between sources of self-efficacy, self-efficacy and writing skills, and to test for gender differences in these indicators. The 155 students (52.2% female) who participated in this study answered to the Sources of Self-Efficacy scale, the Self-efficacy for Writing Scale, and wrote an argumentative text. The Portuguese scale can be used in the proposed domains and sources of self-efficacy and self-efficacy explain writing performance. Girls had higher scores than boys in sources of self-efficacy and in writing performance. Finally, we highlight the role of teachers as models, persuasion agents and promoters of self-efficacy in writing.